MEMBANGUN SISTEM INFORMASI PENGELOLAAN ALAT TULIS KANTOR (ATK) BERBASIS WEB - Nugraha, Deny Wiria (MEKTEK, 2012)
This study aims to establish a management information system web-based office stationery which is expected to help accelerate the process of reporting the use of stationery, and reducing the error information that willgenerate reports that can be accounted for.Based on the test results can be proved that the management information system web-based office stationery that is built to run well, it is characterized by the existing menus to work properly, the data entered into the database properly stored, and application update, insert, and select the database has been connected to the well too.